Analysis of the properties of the self-compacting concrete mixed with tire rubber waste based on design of experiments. (October 2021) - Werdine, Demarcus; Oliver, Guilherme Antonio; de Almeida, Fabricio Alves; de Lourdes Noronha, Mirian; Gomes, Guilherme Ferreira
Abstract: The increase of high demand of technological innovation in building construction have increasingly the need materials that have special structural characteristics. Notably, the use of self-compacting concrete (SCC) has been described by many researchers and engineers as a major revolution in concrete technology due to its fluidity and viscosity characteristics, besides providing energy savings during its construction. Tire waste rubber (TWR) is one of the most important residues that cause serious environmental issues. Recycling TWR in the form of aggregates as supplementary construction material is advantageous in many building fronts. To obtain an optimal SCC manufacturing parameters, this research was based on the application of design of experiments. Several mixtures, or designs, were prepared with different TRW proportions (10%, 30% and 50%). In addition, the effect of the rubber grain size was also considered in the model in two different levels. The specimens were submitted to quasi-static and dynamic tests in order to evaluate their structural performance. The considered responses were the natural frequency, damping factor, compression strength and elastic modulus for different curing periods (7 and 28 days). Statistical results showed the significance of the rubber, grain and curing time for the responses, especially for the strength and elastic modulus. The results of this paper could be a guideline for engineers using SCC in building field.